Irish dimensions in British education: report on 5th national conference, 20 February 1988 - Irish Studies Workshop, ISW; British Association for Irish Studies, BAIS (1988)
Report on the conference, including press cuttings, adverts, list of attendees, leaflet for British Association for Irish Studies and bibliography. Published by Soar Valley College Irish Studies Workshop, Leicester.